Investigation of the influence of a relief of Stavropol Krai on dynamics of thermal convection - Nina Evgen’evna Polyanskaya; Rober Gurgenovich Zakinyan (Наука. Инновации. Технологии)
The article influence of a relief on dynamics of thermal convection that is very important at definition of a condition of the atmosphere is considered. The accounting of heterogeneity of a relief of the Stavropol Krai will allow to predict the phenomena, being accompanied intensive convective processes.